Fermentasi Nira Nipah Menjadi Bioetanol Menggunakan Saccharomyces Cerevisiae Dengan Penambahan Urea Sebagai Sumber Nitrogen - Rahmah, Yulia; Bahri, Syaiful; Chairul, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Nypa is one of biomass wich has a potential to be converted into bioethanol. Bioethanol produced through the process of fermentation of glucose with the help of a microorganism. In this research, nypa sap was converted to be bioethanol using Saccharomyces cerevisiae. The purpose of this researches were doing the fermentation of nypa sap to produce bioethanol, to study the influence of the addition nitrogen source in the fermentation process, and obtain the optimum fermentation time to bioethanol production. The sequances of this research were preparation of material, equipment sterilization, making the starter (inoculum), making the medium fermentation and fermentation process. Fermentation takes place in batches with a volume of 2 liters of fermentation medium. Variation of urea were used 0,2; 0,4; 0,6; and 0,8 g/l, variation of fermentation time were 24, 36, 58, 60, and 72 hours. Temperature fermentation was occured at room temperatur (25 – 30oC). Ethanol concentration was analyzed by using Gas Chromatography. The highest bioethanol concentration was 7,12% at variation of urea 0,6 g/l and fermentation time 36 hours.Keywords : bioethanol, fermentation, nypa sap, Saccharomyces cerevisiae, urea